(untitled) (INTEGRATION PROCEEDING, 2023)
Covid-19 is highly transmittable disease caused by viral infection. Children belong to the age groupvulnerable to the transmission of COVID-19. Health promotion is very important in the midst of the Covid-19 pandemic. Health promotion cannot be separated from the use of media in conveying information. This study aims to determine the knowledge of respondents who were given health education through the games media of snakes and ladders and power point and to find out the differences in knowledge between the two media.This research is aquantitative research with a quasi-experimental research method with a non-equivalent control group design. This research was conducted at SDN Aranio 01, Banjar Regency, South Kalimantan Province, with 23 students in grades IV, V and VI. Data analysis used the Wilcoxon signed ranks test and U-mann Whitney. The results showed that there was an increase in pretest and posttest scores in the snakes and ladders media group with an average pretest of 11.50 and an average of 13.75 in the posttest, while the power point group had an average of 13.09 in the pretest and posttest average 13.73. The Wilcoxon test in the snakes and ladders game media group showed a p value of 0.005 and in the power point group 0.475. This study shows that there is no difference in knowledge of the two media used with statistical results showing a p value of 0.777. The results of the study show that the use of snakes and ladders game media has more influence on increasing elementary school students’ knowledge about preventing Covid-19.